Kill anything that moves [compact disc, unabridged] : the real American war in Vietnam - Turse, Nick (American empire project., 2013)
Based on classified documents and interviews, a controversial history of the Vietnam War argues that American acts of violence against millions of Vietnamese civilians were a pervasive and systematic part of the war.